CSS cookbook - Schmitt, Christopher (O'Reilly, 2006)
As the industry standard method for enriching the presentation of HTML-based web pages, Cascading Style Sheets (CSS) allow you to give web pages more structure and a more sophisticated look. But first, you have to get past CSS theory and resolve real-world problems. For those all-too-common dilemmas that crop up with each project, CSS Cookbook provides hundreds of practical examples with CSS code recipes that you can use immediately to format your web pages. Arranged in a quick-lookup format for easy reference, the second edition has been updated to explain the unique behavior of the latest browsers: Microsoft's IE 7 and Mozilla's Firefox 1.5. Also, the book has been expanded to cover the interaction of CSS and images and now includes more recipes for beginning CSS users. The explanation that accompanies each recipe enables you to customize the formatting for your specific needs. With topics that range from basic web typography and page layout to techniques for formatting lists, forms, and tables, this book is a must-have companion, regardless of your experience with Cascading Style Sheets.